Nordic banks’ entry into the Russian market: motives, processes and challenges - Vornanen, Josefiina (My University, 2013)
The importance of services in the global economy has grown steadily in the past decades and the growth of services sector’s direct investments has been increasing. Nowadays, all companies are influenced by the much changing global environment and the financial services companies are no exception. The internationalization of financial services companies is an expanding and accelerating phenomenon which has various motivations. The overall aim of this thesis is to shed light on the market entry processes of the Nordic financial services companies when they have entered the Russian market. In this study, the factors affecting Nordic banks’ market entry to Russia are presented in order to better understand what have been the main motives for market entry, what kind of processes the banks have used and what kind of challenges they have faced along the way. A case study approach was used in conducting the empirical research and it aims at investigating a specific case: Nordic banks’ entry into the Russian market. The empirical research was carried out by conducting qualitative interviews for employees involved in entry processes of the case banks. These interviews aimed at examining the Nordic banks’ motives for entering the Russian financial market. This includes reflections on the reasons why the studied banks have decided to enter Russia and what have been the motives behind these decisions. Also, the market entry processes the banks have used when they have entered the Russian market were investigated. The findings allowed comparing the related theories and different market entry modes the case banks have used. Furthermore, the market-related challenges faced by the case banks were mapped and described. In addition, the main factors related to the entry processes of the studied banks were identified and key elements of successful market entry were mapped. The findings suggest that the main motivator for banks have been to follow their customers and hence, increase the revenues and add the value to the shareholders; consequently, being a win-win-win situation to all the related parties. It was also discovered that the banks market entry processes have had resemblances but the banks have taken different paths to get where they are nowadays. As the Russian market environment differs from the one in Nordic countries, also challenges were faced by the case banks. However, the internal challenges were considered more troublesome than the external ones. As the foreign market entry process is complex as well as time and resources consuming, it is vital to understand the specifics of the target market, organizational capabilities and individuals enabling a successful entry process.